Investigating The Nexus of Child Marriage and Economic Growth in Indonesia - Rohman, Muhammad Syaikh; Purwono , Rudi; Ramdaniyah, Nurul Fitri (Universitas Airlangga, 2024)
The issue of ending child marriage attracts global attention, especially in developing countries. However, the link between married children and economic growth remains in question. The purpose of this article is to utilize regional macroeconomic indicators to quantify the association between child marriages and the Indonesian economy. The analysis shows a negative relationship between marriage at a young age and the economy using panel regression and simultaneous equations model. The results also demonstrate that marriage at an early age might decrease economic growth, as it has an undesirable effect on health and education. Therefore, this paper delivers a suggestion related to the policy strategies, primarily educational policies and health, that support the Indonesian Government in ending child marriage.